Exploring HIV Risk and Ex-Offender Status Among African American Church Populations: Considerations for Faith-Based Settings. (April 2017) - Berman, Marcie; Berkley-Patton, Jannette; Booker, Alexandria; Bowe-Thompson, Carole; Bradley-Ewing, Andrea
Studies with the general population indicate that involvement in the correctional system is strongly associated with the risk of contracting HIV and other sexually transmitted infections. However, limited studies have examined ex-offender status and HIV risk among African Americans—a population disproportionately impacted by incarceration and HIV—and even fewer have examined these risks among African American church-affiliated populations. This study examined ex-offender status, HIV risks, and perceptions of church involvement in HIV prevention strategies among 484 participants affiliated with African American churches. Findings indicate ex-offender participants were more likely to have been tested for HIV and believed the church should be involved in HIV prevention strategies. Future research, practice, and recommendations on the design of culturally and religiously tailored interventions for ex-offender HIV prevention, screening, and linkage to care in African American church settings are discussed.